(3EMjGA Ydhe GdOjfs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3jHOC CKfGA QHY GdegdcGJ Cf jMJed GdQLd GdTjA ai jOg jchf egfGI dCgdg jOaY Hg GdcHQ Yf faSg s
(3BNQgG (B:s
(3jfJgi GKfGA GdUfa GdQGHY CQHGH GdCehGd hGdeZJQjf efge aQb GdfGS gdci EdG GdYGdehfq s
(3bWYI ef GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B23s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs